Up-Regulation of plant defense genes in harvested mango using electron beam irradiation - Nguyen, Truc Trung; Kato, Masaya; Ma, Gang; Zhang, Lancui; Uthairatanakij, Apiradee; Srilaong, Varit; Laohakunjit, Natta; Jitareerat, Pongphen (Agriculture and Natural Resources, 2022)
Postharvest disease is a major problem in harvested mango fruit, affecting both quantity and quality during storage. Electron beam (E-beam) irradiation is a new approach that enhances plant disease resistance and controls postharvest disease development. This study investigated the effect of pre-treatment with E-beam irradiation on disease development and defense genes expression in mango fruit during cold storage. Mango fruit samples cv. ‘Nam Dok Mai Si Thong’ were pre-treated with an E-beam at a dose of 0 (control) or 0.5 kGy and then stored at 13°C for 16 d. The results at 16 d showed significant reductions in the postharvest disease (anthracnose) incidence of the E-beam treated fruit by 2.0-fold relative to the control (100% and 50% in the control and the E-beam treated group, respectively). Disease severity was also reduced by 3.7-fold (score 2.05 for the control and 0.56 for the treated group). The E-beam treatment up-regulated the expression of plant defense genes, such as MiPOD, MiGLU, MiPAL and MiCHI, in both the peel and the pulp. This suggested that pre-treatment with E-beam irradiation is promising to enhance postharvest disease resistance, which would help to extend the shelf life of mango fruit during cold storage.